Predictive accuracy of single‐ and multi‐slice MRI for the estimation of total visceral adipose tissue in overweight to severely obese patients. (25th March 2015) - Schaudinn, Alexander; Linder, Nicolas; Garnov, Nikita; Kerlikowsky, Felix; Blüher, Matthias; Dietrich, Arne; Schütz, Tatjana; Karlas, Thomas; Kahn, Thomas; Busse, Harald
<x xml:space="preserve">Abstract</x> The quantification of visceral adipose tissue (VAT) is increasingly being considered for risk assessment and treatment monitoring in obese patients, but is generally time‐consuming. The goals of this work were to semi‐automatically segment and quantify VAT areas of MRI slices at previously proposed anatomical landmarks and to evaluate their predictive power for whole‐abdominal VAT volumes on a relatively large number of patients. One‐hundred and ninety‐seven overweight to severely obese patients (65 males; body mass index, 33.3 ± 3.5 kg/m2; 132 females; body mass index, 34.3 ± 3.2 kg/m2) underwent MRI examination. Total VAT volumes (VVAT‐T) of the abdominopelvic cavity were quantified by retrospective analysis of two‐point Dixon MRI data (active‐contour segmentation, visual correction and histogram analysis). VVAT‐T was then compared with VAT areas determined on one or five slices defined at seven anatomical landmarks (lumbar intervertebral spaces, umbilicus and femoral heads) and corresponding conversion factors were determined. Statistical measures were the coefficients of variation and standard deviations σ1 and σ5 of the difference between predicted and measured VAT volumes (Bland–Altman analysis). VVAT‐T was 6.0 ± 2.0 L (2.5–11.2 L) for males and 3.2 ± 1.4 L (0.9–7.7 L) for females. The analysis of five slices yielded a better agreement than the analysis of single slices, required only a little extra time (4 min versus 2 min) and was substantially faster than whole‐abdominal assessment (24 min). Best agreements were found at intervertebral spaces L3–L4 for females (σ5/1 = 523/608 mL) and L2–L3 for males (σ5/1 = 613/706 mL). Five‐slice VAT volume estimates at the level of lumbar disc L3–L4 for females and L2–L3 for males can be obtained within 4 min and were a reliable predictor for abdominopelvic VAT volume in overweight to severely adipose patients. One‐slice estimates took only 2 min and were slightly less accurate. These findings may contribute to the implementation of analytical methods for fast and reliable (routine) estimation of VAT volumes in obese patients. Copyright © 2015 John Wiley & Sons, Ltd.